2021
DOI: 10.3390/antiox10040613
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects against Retinal Degeneration by Centella asiatica Extract (CA-HE50) and Asiaticoside through Apoptosis Suppression by the Nrf2/HO-1 Signaling Pathway

Abstract: Age-related macular degeneration (AMD) is caused by the chronic and gradual oxidative degeneration of the retina. Unfortunately, the general purpose of current treatments is to slow AMD progression, as the retina cannot be restored to its pre-AMD condition. We aimed to identify natural products that can be potential treatments that prevent AMD and can delay the development of late-AMD and selected Centella asiatica extract (CA-HE50), which shows excellent efficacy in cytoprotection. In animal experiments using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…With the improvement of understanding of asiaticoside, multiple functions of asiaticoside have been revealed. Not only capacity of anti-aging in UV damaged cells as reported in the present study, but also capability against retinal degradation and ameliorate inflammation through Nrf2/HO-1 pathway and TLR4/NF-κB pathway, respectively (57,58). Furthermore, asiaticoside-contained foam dressing, nano-composite and nanofibrous scaffold have been developed for traumatic treatment, showing great potential of asiaticoside in wound healing (14,59,60).…”
Section: Discussionsupporting
confidence: 63%
“…With the improvement of understanding of asiaticoside, multiple functions of asiaticoside have been revealed. Not only capacity of anti-aging in UV damaged cells as reported in the present study, but also capability against retinal degradation and ameliorate inflammation through Nrf2/HO-1 pathway and TLR4/NF-κB pathway, respectively (57,58). Furthermore, asiaticoside-contained foam dressing, nano-composite and nanofibrous scaffold have been developed for traumatic treatment, showing great potential of asiaticoside in wound healing (14,59,60).…”
Section: Discussionsupporting
confidence: 63%
“…48 Natural product Centella Asiatica extract suppresses RPE cell apoptosis and protects the retina from degeneration by up-regulating the Nrf2/HO-1 signalling pathway. 49 The current in vitro cell experiments showed that the LBW-95E could significantly improve the survival rate of ARPE-19 cells from oxidative stress which was the main active fraction of LBW. Its mechanism might be related to promoting the translocation of Nrf2 into the nucleus, increasing the levels of intracellular HO-1, SOD and GSH and reducing the level of intracellular ROS.…”
Section: Papermentioning
confidence: 84%
“…CA-HE50 showed a protective effect by inhibiting the expression of inflammatory genes in an APAP-induced liver injury model [29]. Moreover, in a study on the prevention of retinal degeneration of CA-HE50, it was confirmed that CA-HE50 and its active compound, asiaticoside, promote the Nrf2/HO-1 signaling pathway [61]. Judging from the results of these studies, the hepatoprotective efficacy of CA-HE50 shown in the LPS/D-gal-induced ALF animal model is expected to occur through the Nrf2/HO-1 signaling pathway, a well-known antioxidant mechanism.…”
Section: Discussionmentioning
confidence: 87%